2019
DOI: 10.26525/jtfs2019.31.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anatomical Characteristics and Wood Density on Surface Roughness and Their Relation to Surface Wettability of Hardwood

Abstract: Adhesion capability of timbers varies greatly depending on anatomical structure and origin of the species. Unlike temperate hardwood, tropical hardwood has slightly different anatomical structure due to the influence of growing season. This study evaluates the anatomical structure of three tropical hardwood species of different densities, namely, batai, sesendok and kedondong and their effects on surface roughness and wettability. Rubberwood was used as control. The fibre length, wall thickness, lumen diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…On the other hand, batai has the shortest, thinnest fibre, and large vessel diameter (Table 1) which contribute to the lower density. Similar result was also reported by [29] and [30] where density is correlated to the fibre length, fibre wall thickness, and vessel diameter. In terms of shrinkage (Table 2), batai and sesendok have the highest shrinkage for tangential, radial, and longitudinal.…”
Section: Physical and Mechanical Propertiessupporting
confidence: 91%
“…On the other hand, batai has the shortest, thinnest fibre, and large vessel diameter (Table 1) which contribute to the lower density. Similar result was also reported by [29] and [30] where density is correlated to the fibre length, fibre wall thickness, and vessel diameter. In terms of shrinkage (Table 2), batai and sesendok have the highest shrinkage for tangential, radial, and longitudinal.…”
Section: Physical and Mechanical Propertiessupporting
confidence: 91%
“…Previously, Setter et al [26] indicated that the forest species' density and porosity influence the mechanical resistance to shear. In the same way, Alia-Syahirah et al [27] reported that a higher density can negatively affect adhesion in wood products. Despite these preceding studies, wood density was discarded as a negative factor because all the species showed a similar density value.…”
Section: Discussionmentioning
confidence: 80%
“…The first is wettability, the adhesive's capacity to establish contact with the wood surface. This property plays a crucial role in the ability of liquid sealants to spread and infiltrate wood cells, ultimately impacting the bonding strength between the two surfaces [27]. In this step, the adhesive molecules interact with the wood surface through molecular forces such as Van der Waals, hydrogen bonding, and dipole-dipole interactions [32].…”
Section: Discussionmentioning
confidence: 99%
“…The void size in the wood may influence surface roughness. Wood with a larger lumen and diameters would usually result in open grain after machining, which leads to higher surface roughness (Syahirah et al, 2019). In this work, surface roughness of the woods tested should be important for determining its SFE and wettability for both water-based acrylic and oil-based alkyd varnish.…”
Section: Surface Roughnessmentioning
confidence: 99%